Recent applications of conductivity detection in capillary and chip electrophoresis - Solínová, Veronika; Kasicka, Václav (Journal of separation science, 2006)
The review provides a comprehensive survey of the recent applications of contact and contactless conductivity detection in capillary electrophoretic and chip electrophoretic analyses of a broad scale of compounds, from low-molecular-mass highly mobile small inorganic and organic ions, via medium-molecular-mass peptides and oligo- and polynucleotides up to high-molecular-mass biopolymers, proteins and nucleic acids fragments. The review presents also the recent developments in the construction of different types of conductivity detectors (detectors with galvanic contact of the sensing electrodes with the BGE and sample components, contactless conductivity detectors with capacitively coupled tubular and semitubular electrodes and combined conductivity/optical detectors) applied in the capillary electromigration methods performed in classical fused silica, polytetrafluorethylene, and polyetheretherketone capillaries or on glass and polymethylmethacrylate microchips. In addition, the principle and theoretical bases of conductivity detection in capillary electromigration techniques, zone electrophoresis, ITP, micellar EKC, and electrochromatography are briefly described.
Keywords: elektroforéza kapilární; elektroforéza mikročipová; Electrodes; Electrophoresis, Microchip; elektrody; senzitivita a specificita; Sensitivity and Specificity; Electric Conductivity; elektrická vodivost; Electrophoresis, Capillary